2020
DOI: 10.1016/j.molmet.2020.101079
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity causes fetal hypothalamic insulin resistance and disrupts development of hypothalamic feeding pathways

Abstract: Objective Perinatal exposure to maternal obesity results in predisposition of offspring to develop obesity later in life. Increased weight gain in offspring exposed to maternal obesity is usually associated with hyperphagia, implicating altered central regulation of food intake as a cause. We aimed to define how maternal obesity impacts early development of the hypothalamus to program lasting dysfunction in feeding regulatory pathways. Methods Mice offspring of diet-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 58 publications
1
48
0
1
Order By: Relevance
“…Recently, Dearden et al were able to demonstrate specific hypothalamic effects on the proliferative capacity of neurons. In this study, maternal overnutrition in mice resulted in decreased expression of proliferative gene markers, Bub1b, Ki67, and Pcna, coupled to reduced proliferation of neural progenitor cells (61). Furthermore, Kim and colleagues identified increased proliferation in astrocytes, suggesting overall changes in proliferative capacity in different cellular populations of the CNS (62).…”
Section: Neurogenesismentioning
confidence: 70%
“…Recently, Dearden et al were able to demonstrate specific hypothalamic effects on the proliferative capacity of neurons. In this study, maternal overnutrition in mice resulted in decreased expression of proliferative gene markers, Bub1b, Ki67, and Pcna, coupled to reduced proliferation of neural progenitor cells (61). Furthermore, Kim and colleagues identified increased proliferation in astrocytes, suggesting overall changes in proliferative capacity in different cellular populations of the CNS (62).…”
Section: Neurogenesismentioning
confidence: 70%
“…[ 41 ] The neurogenesis of hypothalamus in neonates of HFD dams was reduced [ 42 ] and hypothalamic insulin resistance may contribute to the reduced proliferation of neural progenitor cells. [ 43 ] Besides, insulin signaling inactivation through PDK1 knockout in AgRP neuron downregulated hypothalamic GHRH expression, which was rescued by transactivation‐defective FoxO1. [ 14 ] In our study, maternal MFGM‐PL supplementation significantly increased the expression of hypothalamic GHRH in HFD offspring, which may be particularly relevant to the altered insulin sensitivity in hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…109 A more recent study has reported that fetuses of obese dams display reduced expression of proliferative genes in the hypothalamus and disrupted neurosphere growth and that these two surrogate markers of neuronal proliferation were correlated with maternal insulin levels. 110 Insulin resistance in the developing hypothalamus, including from alterations in insulin receptor DNA promoter methylation, could explain the reduced neuroproliferative response of hypothalamic neurones to insulin in pups exposed to a maternal obesogenic environment. [110][111][112] A role for insulin in glial cell development has also been suggested.…”
Section: Neurode Velopmental Effec Ts Of Insulinmentioning
confidence: 99%
“…110 Insulin resistance in the developing hypothalamus, including from alterations in insulin receptor DNA promoter methylation, could explain the reduced neuroproliferative response of hypothalamic neurones to insulin in pups exposed to a maternal obesogenic environment. [110][111][112] A role for insulin in glial cell development has also been suggested. Insulin levels during early postnatal life are positively correlated with the number of astrocytes.…”
Section: Neurode Velopmental Effec Ts Of Insulinmentioning
confidence: 99%